1981
DOI: 10.1111/j.1399-6576.1981.tb01699.x
|View full text |Cite
|
Sign up to set email alerts
|

Naloxone does not Antagonize the Anesthetic‐Induced Depression of Nociceptor‐Driven Spinal Cord Response in Spinal Cats

Abstract: The effects of several anaesthetics on spinal cord nociceptive neural mechanisms and their interactions with the opiate antagonist, naloxone, were studied in acute, spinal cord transected cats. Intra-arterial injection of bradykinin was used as the noxious test stimulus. Spontaneous activity and the neural response induced by bradykinin were recorded by the multi-unit activity technique in the lateral funiculus of the spinal cord. Naloxone, 0.1 or 2.0 mg/kg i.v. had little effect on the bradykinin-induced resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1986
1986
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…This suggests that low concentrations of halothane may not modulate the nociceptive responses of DH WDR neurons and SMUs EMG responses via spinal opioid µ‐receptors; in a previous investigation in our laboratory, naloxone similarly failed to affect the nociceptive responses of DH WDR neurons and of SMUs during 1% halothane‐induced anaesthesia in intact rat (You et al ., 2005). In addition, some studies have reported that general anaesthesia‐induced inhibition of nociceptive responses is insensitive to naloxone (Harper et al ., 1978; Shingu et al ., 1981). Accordingly, we could suppose that different concentrations of halothane may modulate the spinal signal transmission in the spinal DH area via different spinal multireceptors.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that low concentrations of halothane may not modulate the nociceptive responses of DH WDR neurons and SMUs EMG responses via spinal opioid µ‐receptors; in a previous investigation in our laboratory, naloxone similarly failed to affect the nociceptive responses of DH WDR neurons and of SMUs during 1% halothane‐induced anaesthesia in intact rat (You et al ., 2005). In addition, some studies have reported that general anaesthesia‐induced inhibition of nociceptive responses is insensitive to naloxone (Harper et al ., 1978; Shingu et al ., 1981). Accordingly, we could suppose that different concentrations of halothane may modulate the spinal signal transmission in the spinal DH area via different spinal multireceptors.…”
Section: Discussionmentioning
confidence: 99%
“…Recordings in spinally transected animals, and studies in which anesthetic agents are applied selectively to the spinal cord, suggest that direct drug actions on dorsal horn neurons contributes to anesthetic antinociception (Wall, 1967;Kitahata et al, 1975;Namiki et al, 1980;Shingu et al, 1981;Stein et al, 1987;Jewett et al, 1992;Collins et al, 1995;Uchida et al, 1995;Antognini and Carstens, 2002;Soja et al, 2002). A direct spinal action of anesthetics is also consistent with the observations that nociceptive responses of spinal neurons begin to be depressed at barbiturate doses too low to affect brainstem pain inhibitory pathways (Sandkuhler et al, 1987), and that the minimum alveolar concentration (MAC) of isoflurane sufficient to depress movement in response to noxious stimulation is not altered by decerebration or spinal block (Rampil et al, 1993;Rampil, 1994).…”
Section: Introductionmentioning
confidence: 98%